Unveiling the molecular mechanism of sepal curvature in Dendrobium Section Spatulata through full-length transcriptome and RNA-seq analysis - Qu, Xuefeng; Li, Na; Xu, Cong; Huang, Zifeng; Li, Chunyan; Jiang, Yang; Zheng, Guizhao; Fu, Haiping; Zhang, Guangyan; Liu, Chuan (Frontiers in Plant Science, 2024)
The distinctive curvature of sepals and petals in Dendrobium Section Spatulata orchids is a notable feature, though the underlying molecular and cellular mechanisms governing this trait remain unclear. In this study, we analyzed the morphological characteristics of five hybrids and investigated the transcriptomic basis of sepal curvature specifically in hybrid H5, which exhibits pronounced curling in its sepals compared to relatively flat petals. Full-length transcriptomic sequencing assembled a reference transcriptome with 94,528 non-redundant transcripts, while traditional RNA-seq identified 821 differentially expressed genes (DEGs) between sepals and petals, with 72.8% upregulated in sepals. Gene ontology and pathway enrichment analysis revealed significant involvement of DEGs in cytokinesis, cytoskeletal organization, and energy metabolism, suggesting that these processes play key roles in sepal morphogenesis. Notably, myosin II filament organization was implicated in generating the mechanical forces responsible for curling, while enriched metabolic pathways provided energy for these developmental processes. Morphological analysis revealed that the cells in the upper layers of the sepal were smaller and more numerous than those in the lower layers, suggesting that differential cell growth contributes to sepal curvature. Quantitative real-time PCR (qRT-PCR) analysis of selected genes confirmed the differential expression patterns observed in RNA-seq, supporting the reliability of our transcriptomic findings. Our findings highlight the coordination between cellular mechanics, cytoskeletal dynamics, and metabolic regulation in shaping sepal morphology. This study provides novel insights into the molecular regulation of floral organ curvature and offers a framework for future research on the genetic and cellular basis of orchid morphogenesis.